Analysing Tourism Expenses Using Mathematical Modelling - Janzakov Bekzot Kulmamat ugli (Journal of Artificial Intelligence and Digital Economy, 2024)
The article considers the ways a potential tourist would spend his/ her funds in three-day tour package in Samarkand city. For this purpose, a mathematical simulation model based on Monte Carlo method was used. As a result of the analysis, it was found that the total expenses of tourists were greatly influenced by the costs of transport and food.